L’accès à l’emploi des jeunes en France et en Allemagne : nouveaux défis et changements d’échelles - Olivier Giraud (Espace populations sociétés, 2013)
As well as raising constraints associated with Europeanization or with the decentralization of political systems, the increasing importance of recommendations emanating from international and global institutions makes public policy in the areas of employment and training more complex. These multiple rescaling processes transform both the orientation of these policies and their impact on young peoples’ access to employment/the school to work transitions. A comparative analysis focusing on the contrasting cases of France and Germany from the 1980s to the present day shows a tendency to hybridization of both those models. The school to work regimes are becoming more similar through a still hesitant territorialization of that policy domain in both countries. In the German case, the questioning of the role of branches, centralizing tendencies in the general approach to government and the growing influence of institutional regulations and, on the contrary, decentralizing tendencies and the rise of the influence of private actors in the French one, confirm this trend towards more similarity. These hybridization dynamics are occurring in the contrasting socio-economic and demographic contexts of a persistently high rate of youth unemployment in France and of negative population growth in Germany.